2012
DOI: 10.1103/physrevd.86.073007
|View full text |Cite
|
Sign up to set email alerts
|

S4flavoredCPsymmetry for neutrinos

Abstract: A generalized CP symmetry for leptons is presented where CP transformations are part of an S4 symmetry that connects different families. We study its implications for lepton mixings in a gauge model realization of the idea using type II seesaw for neutrino masses. The model predicts maximal atmospheric mixing, nonzero θ13 and maximal Dirac phase δD = ± π 2 .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 59 publications
2
81
0
1
Order By: Relevance
“…[35][36][37][38][39]. The interplay between flavor symmetries and CP symmetries has been generally discussed in [40,41].…”
Section: Jhep12(2014)007mentioning
confidence: 99%
“…[35][36][37][38][39]. The interplay between flavor symmetries and CP symmetries has been generally discussed in [40,41].…”
Section: Jhep12(2014)007mentioning
confidence: 99%
“…The complex invariance condition in (2.1) can be obtained by the means of a CP transformation [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] on the neutrino fields as…”
Section: Complex Extension Of µτ Antisymmetrymentioning
confidence: 99%
“…This combination is trivial in the sense that these two symmetries commute and this feature allows us to avoid the vev alignment problem that requires special treatment in many models with discrete nonabelian flavor symmetries. 1 In fact, CP µτ can be successfully implemented, sometimes accidentally, in models with discrete flavor symmetries [12][13][14][15][16][17]. More recently, it was shown that maximal θ 23 and maximal Dirac CP phase can be obtained without the explicit imposition of a CP symmetry [18,19] at the JHEP01(2017)068 expense of requiring vev alignment and losing the predictions for the Majorana phases.…”
Section: Introductionmentioning
confidence: 99%